The development of biofeedback photoplethysmograph (electrocardiograph) detection device and simulation application to detect and simulate emotional performance (PERKASA 1) - Abdul Wahab, Muhammad Nubli; Ahmad, Noraziah; Abdalla, Ahmad N (2011)
Biofeedback devices are used more extensively in various applications. The use of biofeedback technology is pioneered by the West. This study was undertaken to develop a biofeedback tool using technology expertise in Malaysia. This study aims to develop a biofeedback device using photoplystmograph technique that measures individual pulse rate, analyzes emotional status and displays it performance on the computer screen. This research uses a sensor that has been modified to detect the pulse of the individual, analyzing the received data to see whether the individual is in a good, medium or weak within the emotional spectrum. The status of this emotional spectrum is displayed by the computer software that has been developed to respond due to user's emotions. This research is also developed biofeedback simulation software that uses cultural background of Malaysia. The result from the hardware and software, of this study has successfully detect the status of individual emotion either in low, mid and high coherence. This tracking system is important as a basis for developing other applications that use biofeedback techniques as a medium. This technology can be further developed and used in a variety of conditions which requires measurement of an individuals emotion.